SYSTEMATIC ANALYSIS OF OCCUPATIONAL SAFETY MANAGEMENT IN INDUSTRIAL ENTERPRISES - Rakhimov Oktyabr Dustkabilovich; Yarasheva Manzura Yakhshiboy kizi (Bright Mind Publishing, 2025)
The article presents information on the role of risk in occupational safety management at industrial enterprises, a systematic approach to safety management, life cycle stages, and management functions. Methods for constructing activity decomposition based on systematic analysis and analyzing the “Cause and Risk Tree” system are covered.
Keywords: Industrial enterprise, safety, management, system, decomposition, systematic analysis, component, ergatic system, operator, “cause-risk-effect” tree, man-machine-environment system.